921 Position statement of the icoh working group on 'emergency preparedness and response in occupational health (eproh)'. (24th April 2018) - Descatha, Alexis; Schunder-Tatzber, Susanne; Burgess, Jefferey; Cassan, Pascal; Kubo, Tatsuhiko; Rotthier, Sylvie; Wada, Koji; committee, EPROH scientific; Baer, Michel
Abstract : Introduction: The Emergency Preparedness and Response in Occupational Health (EPROH) scientific committee was developed to raise awareness of emergency risks for workers, to train managers, employees, and medical staff to prepare for and prevent accidents, acute medical events and disasters, and to mitigate their impact. The committee proposes a position statement on the fundamental need for prevention, response, first-aid treatment, and care in the field of occupational health care. Methods: This position statement was developed following Evidence Based Medicine principles, including literature review, practice networking, and surveys including workers' expectations. Result: The scope of the EPROH group will be focused on Emergency Plans, Procedures, Preparedness, and Training. To ameliorate the dramatic situation of workplace fatalities and accidents/events, EPROH experts have developed recommendations for what every worker should expect in case of a medical emergency, work-related or not, minor or major, while working for his/her company. Minimum response plans for every workplace include information about initial management and contact information. First aid must be encouraged, and occupational health and safety professionals will have to develop procedures that detail responses to emergencies, from minor events to major disasters. As needed, emergency providers should be followed up regularly by an occupational specialist for extended intervals after an event. Discussion: Although global harmonisation, local adaptation, and additional research are needed, this position statement emphasises the importance of having a global statement on the multiple aspects of emergency preparedness and response in occupational settings for every worker everywhere in the world.